Experimental performance analysis of a direct-expansion solar-assisted heat pump water heater with R134a in summer - Kong, Xiangqiang; Sun, Penglong; Dong, Shandong; Jiang, Kailin; Li, Ying (International journal of refrigeration, 2018)
•A direct-expansion solar-assisted heat pump for domestic hot water supply was built.•A series of experiments were carried out under typical summer weather conditions.•The effects of various parameters on the system thermal performance are analyzed. A direct-expansion solar-assisted heat pump (DX-SAHP) system for domestic hot water supply was built and tested, which mainly consisted of a bare flat-plate collector/evaporator with a surface area of 2.1 m2, a variable-frequency rotary-type hermetic compressor, a hot water tank with the volume of 0.2 m3 surrounded by a micro-channel condenser, and an electronic expansion valve. A series of experiments were carried out to test the system performance under typical summer weather conditions in Qingdao, China. The effects of various parameters, including solar radiation intensity of 258–634 W·m−2, ambient temperature of 28–34 °C, compressor speed of 2500–6000 rpm and final water temperature of 50–60.3 °C, on the system performance are analyzed. Experimental results show that the system coefficient of performance(COP) could be enhanced with the increase of the solar radiation intensity or the ambient temperature, and with the decrease of the compressor speed or the final water temperature.